1986
DOI: 10.1111/j.1365-2621.1986.tb00445.x
|View full text |Cite
|
Sign up to set email alerts
|

Technical note: Effect of low pH preservation on the colour and consistency of tomato juice

Abstract: The changes in colour and consistency are reported for tomato juice produced by low pH preservation and stored under ambient conditions. The juice preserved under acid conditions showed higher consistency, probably due to the higher concentration of pectin and the presence of low methoxyl pectin. The furfural and hydroxymethylfurfural which were detected in the juice indicated that darkening of the juice colour was due to non-enzymic browning involving both ascorbic acid and sugars (hexoses). Although the rete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
(6 reference statements)
1
3
0
Order By: Relevance
“…These results are consistent with studies on blanching which show the highest average losses of vitamin C for tomatoes, spinach, broccoli and relatively lower amounts for legumes [25]. Studies have shown that destruction of ascorbic acid is directly related with temperature and air [26,27]. Some researches support the common perception that fresh vegetables are often best for optimal vitamin C content, as long as the fresh product undergoes minimal storage at either room or refrigerated temperatures [27].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These results are consistent with studies on blanching which show the highest average losses of vitamin C for tomatoes, spinach, broccoli and relatively lower amounts for legumes [25]. Studies have shown that destruction of ascorbic acid is directly related with temperature and air [26,27]. Some researches support the common perception that fresh vegetables are often best for optimal vitamin C content, as long as the fresh product undergoes minimal storage at either room or refrigerated temperatures [27].…”
Section: Discussionsupporting
confidence: 88%
“…Studies have shown that destruction of ascorbic acid is directly related with temperature and air [26,27]. Some researches support the common perception that fresh vegetables are often best for optimal vitamin C content, as long as the fresh product undergoes minimal storage at either room or refrigerated temperatures [27]. Blanching and drying process is not as destructive to ascorbic acid, but continued storage and subsequent cooking of fruit and vegetable products result in significant degradation of the vitamins [28].…”
Section: Discussionmentioning
confidence: 99%
“…Hue angle in the final samples decreased as the insoluble solids increased during concentration in vacuum concentration, except the color of commercial samples (Fig. The color change from vacuum concentration is likely caused by browning due to the Milliard reaction and degradation of ascorbic acid, which occurs during thermal treatments (Mudahar et al 1986;Eichner et al 1996). The color change from vacuum concentration is likely caused by browning due to the Milliard reaction and degradation of ascorbic acid, which occurs during thermal treatments (Mudahar et al 1986;Eichner et al 1996).…”
Section: Colormentioning
confidence: 97%
“…5). The color change from vacuum concentration is likely caused by browning due to the Milliard reaction and degradation of ascorbic acid, which occurs during thermal treatments (Mudahar et al 1986;Eichner et al 1996). The commercial samples had already been retorted, so further mild heat treatment would not greatly affect the color.…”
Section: Colormentioning
confidence: 99%